KEBIJAKAN PEMERINTAH INDONESIA TERHADAP TENAGA KERJA INDONESIA YANG TERDAMPAK COVID 19 DI MALAYSIA TAHUN 2020-2021 - Yogi Miradana Harahap; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
COVID-19 has become a global pandemic affecting various aspects of life worldwide. One of the significantly affected groups is migrant workers, including those from Indonesia working in Malaysia. This research purpose is to determine the impact COVID had on Indonesian migrant workers in Malaysia. The research methodology involved data collection through interviews, surveys, and secondary data analysis. The research findings indicate that the COVID-19 pandemic has had serious economic and social impacts on Indonesian migrant workers in Malaysia. They have experienced a decrease in income due to job terminations, company closures, and reduced demand for migrant labor. Furthermore, they also face higher health risks and limited access to healthcare services. The governments of Indonesia and Malaysia need to collaborate to address the impacts of this pandemic by providing better social protection for migrant workers, ensuring improved access to healthcare services, and supporting economic recovery efforts. This research can provide valuable insights for policies and actions needed to protect and support Indonesian migrant workers in Malaysia during and after the pandemic. KeyWords: Pathogenesis, Clinical Manifestations, COVID-19.